The development of waist circumference percentiles in Singaporean children aged 6.0 - 12.9 years - Wong, Xiao Xuan (2014)
Waist circumference (WC) is an indicator of intra-abdominal fat and correlates better with metabolic risks than body mass index (BMI). This study developed the first WC percentile curves in Singaporean school children aged 6.0-12.9 years. WC, height and weight of 905 Singaporean children (437 boys and 468 girls) aged 6.0 to 12.9 years were measured. The age- and gender-specific WC percentiles were constructed and smoothed using the Least Means Squares method. Results showed that WC and BMI increase with age in both sexes. There is a strong positive correlation between WC and BMI in both sexes. Spearman correlation between BMI and WC is statistically significant at r=.851, p<.05, two-tailed for boys, and r=.760, p<.05, two-tailed for girls. BMI and WC were determined to be highly positively correlated and suggest that WC can be a useful supplement to BMI in obesity-related risk stratification. Further studies with a larger sample size needs to be done to determine the cut-off points for these percentiles for an accurate prediction of obesity-related morbidities for different ages, ethnicity and sex in Singaporean children.